El deteriorament del marc normatiu de les competències lingüístiques del personal sanitari a les Illes Balears. Els seus efectes sobre el règim tuïtiu de la llengua catalana - Ballester Cardell, Maria (Revista de Llengua i Dret, 2025)
Gairebé a punt de complir-se el quarantè aniversari de l’aprovació de la Llei 3/1986, de 29 d’abril, de normalització lingüística de les Illes Balears, continua molt viu el debat sobre el règim de capacitació lingüística del personal sanitari del Servei de Salut. Les successives revisions normatives sobre l’ús de les llengües oficials en aquest àmbit i la resposta judicial, tant respecte a l’establiment del requisit de coneixements de llengua catalana com a l’adopció de mesures potencialment regressives, són una mostra de les dificultats que comporta avançar cap a un marc jurídic estable que garanteixi adequadament els drets lingüístics dels usuaris en l’àmbit assistencial i sanitari. En aquest estudi s’analitzen les tensions provocades per les fluctuacions normatives que s’han produït en les darreres legislatures i la doctrina recent del Tribunal Constitucional en relació amb la rebaixa de les competències lingüístiques del personal sanitari del Servei de Salut de les Illes Balears. Aquestes circumstàncies, en conjunt, marquen una tendència regressiva i fan minvar el nivell de protecció de la llengua catalana a les Illes Balears. , Almost on the eve of the 40th anniversary of the approval of Law 3/1986, of 29 April, on the linguistic normalisation of the Balearic Islands, the debate on the language training regime for health service staff is still very much alive. The successive regulatory revisions on the use of the official languages in this field and the judicial response, with regard to both the requirement to know Catalan and the adoption of potentially regressive measures, are an example of the difficulties involved in moving toward a stable legal framework that adequately guarantees users’ language rights in the healthcare field. This study analyses the tensions caused by the regulatory fluctuations that have occurred in recent legislatures and the recent doctrine of the Constitutional Court in relation to the reduction in the level of language competence required by healthcare staff in the Balearic Islands Health Service. These circumstances, taken together, mark a regressive trend and lower the level of protection of the Catalan language in the Balearic Islands. , Casi a punto de cumplirse el cuadragésimo aniversario de la aprobación de la Ley 3/1986, de 29 de abril, de Normalización Lingüística de las Islas Baleares, continúa muy vivo el debate sobre el régimen de capacitación lingüística del personal sanitario del Servicio de Salud. Las sucesivas revisiones normativas sobre el uso de las lenguas oficiales en este ámbito y la respuesta judicial, tanto con respecto al establecimiento del requisito de conocimientos de lengua catalana como a la adopción de medidas potencialmente regresivas, son una muestra de las dificultades que comporta avanzar hacia un marco jurídico estable que garantice adecuadamente los derechos lingüísticos de los usuarios en el ámbito asistencial y sanitario. En este estudio se analizan las tensiones provocadas por las fluctuaciones normativas que se han producido en las últimas legislaturas y la reciente doctrina del Tribunal Constitucional en relación con la rebaja de las competencias lingüísticas del personal sanitario del Servicio de Salud de las Islas Baleares. Estas circunstancias, en conjunto, marcan una tendencia regresiva y disminuyen el nivel de protección de la lengua catalana en las Islas Baleares.

The language barrier : the overlooked challenge to equitable health care - Hussey, Nadia (South African Health Review, 2012)
This chapter examines the effects of language barriers on the access of patients and communities to quality health care. It also looks at communication challenges experienced by health professionals that provide this care. Using a case study of a rural hospital, the chapter highlights some of the challenges posed by the language barrier and explores current methods that English-speaking health professionals at this hospital use to overcome these difficulties. The case study findings indicate that the language barrier decreases work efficiency and the provision of holistic treatment. It makes communication time consuming, which increases frustration levels and decreases empathy, approachability and confidentiality. Current methods for overcoming problems include the use of untrained and ineffective interpreters - usually overworked nurses; linguistic codeswitching; and the use of a selection of key isiXhosa vocabulary. These methods have many drawbacks and are not suitable or sustainable. Recommendations for improving communication include the promotion of a culture of multilingualism, which includes language education as a part of professional development and the employment of trained interpreters. For multilingualism to occur, more research needs to be conducted, and the political will to address this problem must be demonstrated. Overcoming the language barrier needs to be prioritised and commitment must be made to implementing strategies that provide a multilingual patient base with a multilingual healthcare service.

Communicative sensitivity in the bilingual healthcare setting: A qualitative study of language awareness - Irvine, Fiona. E.; Roberts, Gwerfyl. W.; Jones, Peter; Spencer, Llinos. H.; Baker, Colin. R.; Williams, Cen (Journal of Advanced Nursing, 2006)
Aim. This paper reports on the second phase of a national study in Wales. The research aimed to assess the level of Welsh language awareness amongst healthcare professionals across Wales, and to identify the factors that enhance language choice within service delivery. Background. The literature suggests that language sensitive healthcare practice is central to ensuring high quality care. However, it is evident that language barriers continue to compromise the quality of care within nursing and other health services. One issue that has received little attention is the level of language awareness that healthcare professionals currently demonstrate. Furthermore the factors that influence language choice for bilingual/multilingual speakers are not well explored in the literature. Methods. The study involved semi-structured interviews with a range of healthcare professionals in acute and community settings across Wales. Using a systematic sampling matrix, a purposeful sample of 83 professionals was selected to participate. Twenty-seven of the respondents were nurses, health visitors and midwives. The interviews focussed on the factors that facilitate or impede language sensitive healthcare practice. All interviews were audiotaped and, using a framework analysis approach, conceptual codes were developed and defined and categories and sub-categories were constructed to create thematic charts. Findings. Three main themes were identified: care enhancement, which focussed on the process and outcome of offering language choice to bilingual patients; organizational issues, which reflected issues relating to the infrastructure of service provision; and training implications, which focused on Welsh language learning in health care. Conclusions. Complex dynamics of language use are in operation within bilingual healthcare settings and organizational as well as individual factors are important in facilitating appropriate language use. Many of the issues highlighted are not peculiar to the Welsh context, but apply to healthcare settings across the world, where other minority languages are in use.

Presente, pasado y (sobre todo) futuro de la atención sanitaria en euskera [Present, past and (above all) future of healthcare in Basque] - Zarate Sesma, Jon; Montes, Aitor (Revista de Llengua i Dret, 2025)
Resumen La normalización de la atención sanitaria sería ofrecer una atención integrada basada en la evidencia y centrada en el usuario (paciente), lo que pasa por una atención en el idioma de elección del usuario. Para la consecución de dicha normalización, y teniendo en cuenta la complejidad del sistema sanitario centrado en el usuario, es necesario poner en marcha políticas que apuesten por el impulso de la conciencia lingüística entre los profesionales sanitarios y ofrecer estrategias para asegurar la asistencia sanitaria integral en euskera. Es imprescindible aprobar un nuevo decreto que reemplace el Decreto 67/2003 y que exija como mínimo el nivel C1 en euskera para el ejercicio de la profesión sanitaria. Del mismo modo, habría que registrar el idioma de elección del usuario a través de la oferta activa, impulsar los circuitos sanitarios en euskera (con la identificación de los servicios y profesionales euskaldunes) y poner en marcha la historia clínica en euskera. Resum La normalització de l'atenció sanitària seria oferir una atenció integrada basada en l'evidència i centrada en l'usuari (pacient), la qual cosa passa per una atenció en l'idioma d'elecció de l'usuari. Per a la consecució de l'esmentada normalització, i tenint en compte la complexitat del sistema sanitari centrat en l'usuari, cal posar en marxa polítiques que apostin per l'impuls de la consciència lingüística entre els professionals sanitaris i oferir estratègies per assegurar l'assistència sanitària integral en eusquera. És imprescindible aprovar un nou decret que reemplaci el Decret 67/2003 i que exigeixi com a mínim el nivell C1 d’eusquera per a l'exercici de la professió sanitària. Així mateix, caldria registrar l'idioma d'elecció de l'usuari a través de l'oferta activa, impulsar els circuits sanitaris en eusquera (amb la identificació dels serveis i professionals bascoparlants) i posar en marxa la història clínica en eusquera. Abstract Healthcare normalisation should involve evidence-based and user (patient)-centred integrated care, provided in the user’s language of choice. To achieve this normalisation, and bearing in mind the complexity of the user-centred healthcare system, it is necessary to implement policies that promote language awareness among healthcare professionals and to offer strategies to ensure comprehensive healthcare in Basque. It is essential to pass a new decree to replace Decree 67/2003, requiring a minimum level of C1 in Basque to work as a healthcare professional. The user’s language of choice should also be recorded by the healthcare system, promoting healthcare circuits in Basque (identifying services available in Basque and Basque-speaking professionals) and making medical records available in Basque. Laburpena Osasun-arretaren normalizazioa ebidentzian oinarritutako eta erabiltzailearengan (pazientearengan) zentratutako arreta integratua eskaintzea litzateke, hau da, nahitaez erabiltzailearen aukerako hizkuntzan. Osasun-sistemaren konplexutasunak beharrezkoa egiten du giza kapitalean oinarritutako kultura-aldaketa: hizkuntza-kontzientzia duten langile ekintzaileak. Eztabaida eta paradigma berriak, diskurtso berria, erabiltzailearengan kokatu behar da, eta ez medikuarengan. Etorkizuna, neurri handi batean, osasun-profesionalen artean hizkuntza-kontzientzia sustatzearen aldeko apustua egiten duten politiken mende dago, bai eta osasun-arreta integrala euskaraz bermatzeko estrategiak eskaintzen dituztenen mende ere. Ezinbestekoa da dekretu berri bat onartzea, 67/2003 Dekretua ordeztuko duena eta lanbide sanitarioan jarduteko gutxienez euskarazko C1 maila eskatuko duena. Era berean, erabiltzaileak arretarako aukeratzen duen hizkuntza eskaintza aktiboaren bidez erregistratu beharko litzateke, osasun-zirkuituak euskaraz sustatu beharko lirateke (zerbitzu eta profesional euskaldunak identifikatuta) eta historia klinikoa euskaraz abiarazi beharko litzateke.